EFEKTIVITAS BIMBINGAN PRANIKAH TERHADAP PASANGAN CALON PENGANTIN DALAM MEMBENTbUK KELUARGA SAMAWA DI KUA KECAMATAN JUNREJO - Riadhatun Nabila; Ibnu Jazari; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Problems in the household are often found in society, the causes also vary, strating from mistakes in the past before or after wading through married life. Divorce can occur due to lack of readinees between prospective married couples and less than optimal in conducting premarital guidance. In this study, researcher conducted research at KUA Junrejo District using descriptive research methods, namely case studies. At the premarital guidance program that implemented by the Junrejo District KUA institution in realizing a sakinah, mawaddah and rahmah family for the prospective bride and groom, the bride and groom have met the requirements set out in the Marriage Law, Religion and the decision of the Director General of Islamic Community Guidance. The effectiveness of premarital guidance for the prospective bride and groom in realizing a sakinah, mawaddah dan rahmah family has been effective, it can be seen from the existing criteria, that is the clarity of the goals to be achieved in the premarital guidance program, clarity og strategy, careful planning, good and appropriate preparation of guidance programs, effective and effecient implementation of premarital guidance, the existance of a supervisory system that is educative by the presenters of premarital guidance. Key Words: Effective, Guidance, Premarital, The Household